PSYCHOANALYTICAL ANALYSIS ON HANNIBAL LECTER AND BUFFALO BILL CHARACTERS AS SEEN IN THE SILENCE OF THE LAMBS AND HANNIBAL RISING BY THOMAS HARRIS. - Panji Perdana Putra (English Department, Faculty of Humanities, Andalas University, 2013)
This research descibes about the analysis of the characters in The Silence of the Lambs and Hannibal Rising by Thomas Harris. These characters is very interesting to be analyze because they appeared the similarity in serial killer, and also the diffrences in style. Both of them, comparing in the development of their pscycological problems by their chilhood traumatic experiences. The writer uses the psychological approach by Sigmund Freud who divided three human psyche zones Id, Ego and Superego. Also the Self Defence Mechanism that proposed by Anna Freud. In this research, the writer applies the qualitative research by using descriptive method. As the result of the analysis, the writer finds that despite of these characters, Buffalo Bill who is the traditional method in serial killer and Hannibal Lecture who is categorized as sophisticated serial killer. Both of them applies their self defence mechanism as the tools to achieve their goals.Keywords: psychoanalysis, self-defense mechanism, sublimation, trauma